Importance of Ahara Vidhi Vidhana (Dietary Guidelines) in Ayurveda - Potter, Bhagya Shree; Sharma, Ashok Kumar; Nigam, Ayushi; Singh, Naval (International Research Journal of Ayurveda & Yoga, 2023)
Ayurveda’s Prayojana strives to protect the health of the healthy and cure issues caused by disease. Numerous factors might affect one’s health and susceptibility to diseases. As the Acharyas had said, the Triupstambha (three sub pillars) of Ahara, Nidraand Brahmacarya support the body itself. In this case, Ahara is named first, showing how important it is to protect and sustain life. A healthy life requires adequate nutrition, yet one cannot benefit fully from the food they consume if they do not follow suitable dietary standards. Acharya Charak provided Aharavidhividhan (dietary recommendations), which can stop many diseases from developing purely as a result of poor dietary practises. Each factor’s scientific basis is described. If the Aharavidhividhana is properly practised, it contributes to better health and a longer life. Additionally important are the Aahara intake’s timing, location, volume, and mode. If taken properly, Aahara promotes healthy body development; however, if taken incorrectly, it can cause a number of problems. As a result, Aharavidhividhanais crucial for both the disease’s cause and its treatment.